A Control Strategy of Multichannel DC/DC Converters with Cross-vehicle Parallel Connection for Urban Rail Vehicles with Wireless Power Transfer - ZHOU Zhenbang; WANG Yue; ZHANG Zhixue; LIU Huadong; PENG Yun; WU Yi (Kongzhi Yu Xinxi Jishu)
A new droop control method is proposed in this paper to solve three problems, the problem of power error caused by the difference of output impedance of DC / DC circuits in the on-board power supply system of non-contact power supply urban rail vehicles, the problem that there is no unified control between carriages, and the problem that each DC/DC circuit does not share the current in the constant current charging control process, respectively. The proposed method guarantees the power distribution accuracy of each vehicle and each DC/DC conversion circuit by modifying the droop coefficient, making it possible for multi-vehicle communication and voltage stabilization, and has better anti-disturbance capability. The reference voltage is improved by introducing a modified fine adjustment to solve the problem of power imbalance. Finally an average current distribution method is proposed to ensure the current sharing of each DC/DC, and is verified by simulation and experiment.